Ausstellung Landesmuseum Zürich : «Sprachenland. Die Schweiz im Spiegel ihrer Sprachen» - 3 Fragen an... (Babylonia, 2023)
In this short interview, Thomas Bochet, Melanie Würth and Maxi Weibel share some insights into this exhibit on the many languages of Switzerland.